Modern radiology in gastroenterology (Аccording to the 19-th Russian gastroenterological week data) - Z. A. Lemeshko (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To carry out analysis of reports and publications devoted to radiological methods of investigation in gastroenterology and to present up-todate options of these methods to doctors-gastroenterologists, experts in radiology and doctors of specialties.Key points. Results of scientific studies and practical application of radiological methods in diagnostics of digestive diseases are presented. Application of radiological methods at detection and differential diagnostics of diseases of the liver, gallbladder, the pancreas, the spleen, gastro-intestinal tract, as well as for patients follow-up and at noninvasive interventions is reflected.Conclusion. Expansion of the range of problems solved with application of radiological diagnostic methods of gastroenterological patients is marked.